Experimental study and evaluation of single slope solar still combined with flat plate collector, parabolic trough and packed bed. (15th January 2020) - Madiouli, Jamel; Lashin, Ashraf; Shigidi, Ihab; Badruddin, Irfan Anjum; Kessentini, Amir
Abstract: This paper experimentally investigates the performance of conventional single slope solar still and the impact of integrating a flat plate collector (FPC) as well as parabolic trough collector (PTC) supported with a packaged glass ball layer (PLGB), which acts as a thermal storage medium to the systems. The incident solar energy from the PTC-FPC is collected by two separate loops of finned pipes acting as heat exchangers in still basin. Experiments were conducted during winter and summer seasons with saline water depth of 50 mm. Results revealed that solar still integrated with PTC, FPC and PLGB has a higher freshwater production rate of 6.036 kg/m 2 /day during summer and 2.775 kg/m 2 in winter. Moreover, FPC-PTC-PLGB solar still found to have increased productivity by 172% in winter and 203% in summer, compared to conventional solar still. The efficiency in winter for the solar still with FPC-PTC-PLGB is found to be 16.24% compared to 21.83% in summer, which is higher than the efficiency of conventional solar still at 8.1% (winter) and 12.15% (summer). An economic analysis was carried out for all different parameters investigated to confirm the feasibility of integration of FPC-PTC-PLGB. The price of one liter water produced from conventional solar still (CSS) was $0.067 whereas for the developed solar still (DSS) it was $0.22.